Proceedings of the 2008 ACM Symposium on Applied Computing 2008
DOI: 10.1145/1363686.1363855
|View full text |Cite
|
Sign up to set email alerts
|

Automatic software fault localization using generic program invariants

Abstract: Despite extensive testing in the development phase, residual defects can be a great threat to dependability in the operational phase. This paper studies the utility of lowcost, generic invariants ("screeners") in their capacity of error detectors within a spectrum-based fault localization (SFL) approach aimed to diagnose program defects in the operational phase. The screeners considered are simple bitmask and range invariants that screen every load/store and function argument/return program point. Their generi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
3

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 24 publications
0
12
0
3
Order By: Relevance
“…Another example of a situation where no reference system is available is when a product has passed the testing stage, and is released on the market. For this situation, in (Abreu et al, 2008a;Abreu et al, 2008b) generic program invariants were successfully used as error detectors for spectrum-based fault localization. The authors concluded that the diagnostic quality of this fully automated approach equals the one obtained when the reference program is used.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of a situation where no reference system is available is when a product has passed the testing stage, and is released on the market. For this situation, in (Abreu et al, 2008a;Abreu et al, 2008b) generic program invariants were successfully used as error detectors for spectrum-based fault localization. The authors concluded that the diagnostic quality of this fully automated approach equals the one obtained when the reference program is used.…”
Section: Related Workmentioning
confidence: 99%
“…The authors concluded that the diagnostic quality of this fully automated approach equals the one obtained when the reference program is used. The investigated program invariants are the bitmask (Abreu et al, 2008a), range (Abreu et al, 2008a; Abreu et al, 2008b), and the Bloom filter (Abreu et al, 2008b) invariants. Given that the performance overhead of generic program invariants is small, they are attractive to be used in the context of resource constraint systems, as the one we used in our industrial experiments, allowing to create self-diagnosing systems.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, we would also like to apply the technique to a broader range of faults. Finally, we also intend to extend the framework with generic, automatic error detection techniques, e.g., [28], to be able to detect more errors.…”
Section: Discussionmentioning
confidence: 99%
“…To address the coincidental correctness problem in coverage-based fault localization approaches, Wang et al [17] prescribe patterns for different types of faults and modify the coverage vectors to locate faults with the feature of coincidental correctness. To solve test oracle problem, Abreu et al [18] apply invariants to SFL and use error detection to judge failures, and Xie et al [19] apply metamorphic testing to SFL to perform SFL without test oracle. It can be seen that current research on SFL usually ignores the interaction between software debugging engineers and fault localization.…”
Section: Related Workmentioning
confidence: 99%